KONTEKSTUALISASI MAKNA JIHAD DALAM POTRET KEINDONESIAAN: ANALISIS HERMENEUTIKA HASSAN HANAFI TERHADAP HADITS TENTANG PERANG - M. Syafiuddin Shobirin (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2020)
The term of jihad in recent years has become an interesting topic of conversation, especially after the term was used by radical groups to carry out acts of terror in the name of religion, and by using arguments from sacred texts, one of which is hadith. This paper aims to examine one of the hadiths which has an extreme meaning,